Molecular Diagnosis of Brettanomyces bruxellensis’ Sulfur Dioxide Sensitivity Through Genotype Specific Method - Avramova, Marta; Vallet-Courbin, Amélie; Maupeu, Julie; Masneuf-Pomarède, Isabelle; Albertin, Warren (Frontiers in Microbiology, 2018)
The yeast species Brettanomyces bruxellensis is associated with important economic losses due to red wine spoilage. The most common method to prevent and/or control B. bruxellensis spoilage in winemaking is the addition of sulfur dioxide into must and wine. However, recently, it was reported that some B. bruxellensis strains could be tolerant to commonly used doses of SO2. In this work, Brettanomyces bruxellensis response to SO2 was assessed in order to explore the relationship between SO2 tolerance and genotype. We selected 145 isolates representative of the genetic diversity of the species, and from different fermentation niches (roughly 70 % from grape wine fermentation environment, and 30% from beer, ethanol, tequila, kombucha, etc.).These isolates were grown in media harboring increasing sulfite concentrations, from 0 to 0.6 mg.L-1 of molecular SO2. Three behaviors were defined: sensitive strains showed longer lag phase and slower growth rate and/or lower maximum population size in presence of increasing concentrations of SO2. Tolerant strains displayed increased lag phase, but maximal growth rate and maximal population size remained unchanged. Finally, resistant strains showed no growth variation whatever the SO2 concentrations. 36% (52/145) of B. bruxellensis isolates were resistant or tolerant to sulfite, and up to 43% (46/107) when considering only wine isolates. Moreover, most of the resistant/tolerant strains belonged to two specific genetic groups, allowing the use of microsatellite genotyping to predict the risk of sulfur dioxide resistance/tolerance with high reliability (>90%). Such molecular diagnosis could help the winemakers to adjust antimicrobial techniques and efficient spoilage prevention with minimal intervention.